Korelasi Antara Kadar Vitamin C dengan Kadar Methemoglobin Darah Lansia di Kecamatan Pakem Kabupaten Sleman - Prasetyastuti Prasetyastuti (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Oxidative damage  by  free  radical can  cause  aging  process. Erythrocyte  as an  oxygen –  carrying agent  has high  risk  of  oxidative  injury which can  inducemethemoglobin  production.  Vitamin C  is  an  exogen antioxidant  that work  in  aqueous  phase  like  blood  and  can  react   with    free  radical before  they  initiate  the oxidative  injury.Objectives: The  aim of  this study was  to  find out whether  there  is possibility  of correlation  between  vitamin C and methemoglobin  level  in blood of elderly  living  in Pakem DistrictMethod:  This was  an observational  research with  cross  sectional  design,  in which  32  elderly  from  Pakem District were  subjects.  The  blood  sample was  taken  from  cubital  vein.  Determination  of   vitamin C  and methemoglobin  level  used  spectrophotometer. Pearson Correlation was  employed  to  analyze  the  data.Results: The vitamin C and methemoglobin level of the elderly 0,43 + 0,25 mg/dl  and  0,035 +  0.02% respectively. The  correlation between  vitamin C  and methemoglobin  level was  not significant    (  p =  0.771).Conclusion: The  vitamin C was not  correlated with  the methemoglobin  level.Keywords: vitamin C, methemoglobin,  elderly,  free  radica